Culture Ministry Meeting G20 Cultural Carnival as an Introduction to the Value of Borobudur Temple Relief - Rio Fernandez Tamba (Universitas Negeri Medan, 2022)
The implementation of the Cultural Carnival at the 2022 G20 Culture Ministers Meeting Series was carried out by taking values from the Jataka of the Borobudur Temple. Not from the implementation of the Cultural Carnival using 20 Jataka reliefs by combining dances, costumes, props, and ogoh-ogoh to be performed. Jataka reliefs is a medium to introduce and instill the value of Jataka reliefs in everyday life. This study uses an approach of processing research data in a descriptive way to explain how to instill the value of the temple's jataka reliefs in implementing the G20 Cultural Carnival. Implementing the CMM G20 Cultural Carnival can be carried out well by presenting performances from 20 villages in Borobudur District using performances in the Cultural Carnival. The results of this study explain the planting of values from the Jataka Reliefs of Borobudur Temple in implementing the production of the Cultural Carnival. This activity gains a positive perspective from character by developing the abilities of local communities and increasing creativity so that it becomes a new type of art that instills value from the Jataka reliefs of Borobudur Temple. The values depicted from each of the fable reliefs of Borobudur Temple are expected to become cultural icons of the community in welcoming tourists visiting Borobudur Temple, Central Java, Indonesia.